Photosynthetic and morphological acclimation of seedlings of tropical lianas to changes in the light environment - Ávalos Rodríguez, Gerardo (2014)
Premise of the study: Few studies have analyzed the physiological performance of different life stages and the expression of ontogenetic niche shifts in lianas. Here, we analyzed the photosynthetic and morphological acclimation of seedlings of Stigmaphyllon lindenianum, Combretum fruticosum, and Bonamia trichantha to distinctive light conditions in a tropical dry forest and compared their response with the acclimation response of adult canopy lianas of the same species. We expected acclimation to occur faster through changes in leaf photochemistry relative to adaptation in morphology, consistent with the life history strategies of these lianas. Methods: Seedlings were assigned to the following light treatments: high light (HH), low light (LL), sun to shade (HL), and shade to sun (LH) in a common garden. After 40 d, HL and LH seedlings were exposed to opposite light treatments. Light response curves, the maximum photosynthetic rate in the field (Amax), and biomass allocation were monitored for another 40 d on leaves expanded before transfer. Key results: Photosynthetic responses, Amax, and biomass of Stigmaphyllon and Combretum varied with light availability. Physiological characters were affected by current light environment. The previous light environment (carryover effects) only influenced Amax. Morphological characters showed significant carryover effects. Stigmaphyllon showed high morphological and physiological plasticity. Sun-exposed seedlings of this liana increased stem biomass and switched from self-supporting to climbing forms. Conclusions: Acclimation in seedlings of these lianas is consistent with the response of adult lianas in the canopy in direction, but not in magnitude. There was no evidence for ontogenetic niche shifts in the acclimation response.